Mapping The Role of Foreign Direct Investment from Major Economies in India’s Gdp Expansion: With Focus on Healthcare Sector - Mor, Reshuka; Saini, Jaswant (Journal of Neonatal Surgery, 2025)
Capital inflows, technological improvements, job creation, and industrial expansion are all fueled by foreign direct investment (FDI), which is a major factor in economic growth. Foreign direct investment (FDI) from a number of important economies has contributed to India's GDP growth; this study seeks to identify those countries and their relative contributions. To examine FDI patterns, sector-specific contributions, and their relationship to GDP growth, the study uses a mixed-method approach, integrating quantitative and qualitative analysis. The research relies on secondary data gathered from various government studies, including those from the OECD, UNCTAD, DPIIT, and the Reserve Bank of India (RBI). Foreign direct investment (FDI) flows vary considerably between economies, according to the statistics, and there is a moderately positive association between FDI and GDP growth. Findings indicate that foreign direct investment (FDI) helps India's economy grow, but that policy-driven oscillations, sectoral inequities, and FDI's overall volatility necessitate steady policies that are good for investors. Notably, the healthcare sector has emerged as a vital recipient of FDI, reflecting rising global interest in India's healthcare infrastructure, services, and medical innovation. To provide long-term economic resilience and sustainable development, the report suggests diversifying foreign direct investment (FDI) sources, encouraging investment in high-growth industries including healthcare, renewable energy, and technology, and strengthening policy frameworks